Holographic texture inspired by the vases of Islamic art - asmaa mohamed khatab (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
It is an important component of its cultural identity and artistic spirit that is unique among civilizations, as it expresses its artists' genius, concealment, and devotion to their art. Islamic art, in turn, contributed to the building of a distinct artistic personality of the society, which was a great sign of the progress of this civilization and the skill of its vanity. This is reflected in one of the elements of this civilization, Islamic art, which is deeply rooted in the human conscience. Islamic pottery is one of the most important arts that Muslims have known in their entire field. At the level of manufacturing techniques, as well as marketing and coloring, chemical preparations were considered during the Middle Period to be the creations of Islamic civilization and one of the most remarkable discoveries of which they were unique in their own era and for many other periods,1The next brother. Others that need to experiment and create a set of variables that will create a new addition that contributes toEnriching this art. Experimentation has given contemporary art the opportunity to explore the formative connections that grow consciousnessIntellectual and artistic formation, which led to a serious and unorthodox form of expression, to find aesthetic solutions suited to contemporary cultural thought.The question here is:_ How is it possible for her to form a textured vessel inspired by Islamic art using thread Flexible, soft wool, without any stents or rigid structures ?